Phygital: An Innovative Model for Developing Receptive Skills in English Through Learner Autonomy - Prasad M.; Seema P.V. (Emerging Trends in Languages, 2025)
The study named “Phygital: An Innovative Model for Developing Receptive Skills in English through Learner Autonomy” tries to establish that it is an innovative scientific model, evidently distinguished from other prototypes such as blended learning, e-learning, flip learning, online learning, hybrid learning etc. The paper also tries to emphasize that it is best suited for the new age learners and that it enhances the receptive skills (listening and reading) in English among the higher secondary school students. The model inevitably promotes learners’ English language proficiency. It incites interest and motivation for learning. This model also promotes individualized learning. The Phygital model has been envisaged as a smart learning ecosystem that promotes learner autonomy, language proficiency, especially receptive skills and e-resources use. Learner autonomy is one of the major aims of education. LA means freedom and flexibility of learning. Learner autonomy is the ability to take charge of one’s own learning. The paper also examines the famous learner autonomy definitions of Holec, Littlewood, Benson, Dickinson etc. The paper also examines the Phygital model theory expounded by Poonsri Vate etc. tried in other fields of learning such as music etc. Phygital model promotes meaningful student engagement and collaborative learning. Phygital model is open, playful and autonomous. Poonsri Vate presents the Phygital model as a concept of a smart learning ecosystem of 8Cs. It has a clear classroom procedures plan as well. The model also analyses the salient features of learner autonomy and the Phygital model. Furthermore it studies the possibility of using digital devices and components along with the learning apps and sites for the promotion of English Language Learning (ELL). The paper concludes that the Phygital model improves learner autonomy and language proficiency, especially receptive skills (listening and reading). This model can be adapted to other subject areas as well. Learners, teachers, educators, researchers and policymakers can adopt the model for imparting quality learning experience and achieving desired outcome.
Keywords: Phygital learning; blended learning; flip learning; hybrid learning; learner autonomy; receptive skills